Hubungan Budaya Organisasi, Kecerdasan Emosional, dan Kepemimpinan Transformasional dengan Tingkat Kepuasan Kerja Pegawai BPBD Kota Tangerang - Ramdani, Ramdani; Eri Marlapa (ATRABIS Jurnal Administrasi Bisnis (e-Journal), 2025)
Job satisfaction is a key requirement in organizations. Job satisfaction is directly related to employee performance, which ultimately affects the smooth running of the organization as a whole. This study aims to analyse the influence of Organisational Culture, Emotional Intelligence, and Transformational Leadership on Job Satisfaction at BPBD Tangerang City. The population in the study was 55 employees. The sample used in this study had 55 employees of BPBD Tangerang City. The sampling method in the study used a saturated sample. The data analysis method used is Partial Least Square (PLS). The results of this study indicate that the Organisational Culture variable has a positive and significant effect on Job Satisfaction, Emotional Intelligence does not have a significant effect on Job Satisfaction, and Transformational Leadership has a positive and significant effect on Job Satisfaction.